POVERTY REDUCTION THROUGH THE FAMILY HOPE PROGRAMME - Airmas, Pita Fitria; Ilato, Rosman; Aneta, Yanti (Public Policy Journal, 2023)
This research aims to find out (1) the Implementation of the Family Hope Programme (PKH) in Poverty Alleviation in Talumolo Village, Dumbo Raya Sub-district, Gorontalo City (2) the Determinant Factors of PKH Success in Poverty Alleviation in Talumolo Village, Dumbo Raya Sub-district, Gorontalo City. This research uses a descriptive qualitative method, while the data collection techniques used are interviews, field observations, and documentation. Based on the results of the research, it is known that the implementation process of the Family Hope Program (PKH) in Poverty Alleviation in Talumolo Village, Dumbo Raya District, Gorontalo City, which consists of Planning, Determination of KPM PKH, Distribution of Assistance, Assistance, and Membership Transformation has been carried out well but there are still obstacles, namely frequent changes in regulations, and the end of PKH membership through the social assistance check application. (2) Determinants of Success in the Implementation of the Family Hope Program (PKH) in Poverty Alleviation in Talumolo Village, Dumbo Raya Subdistrict, Gorontalo City, namely Communication, Resources, Disposition / Attitude of Implementers and Bureaucratic Structure have been carried out well but on the part of the community, there is a lack of participation in attending group meetings and P2K2